2020
DOI: 10.14334/jitv.v25i2.2501
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Some Plant Bioactives as Feed Additives to Replace Antibiotic Growth Promoters in Broiler Feeds

Abstract: Antibiotics (AGP) have been used as feed additives to promote growth and feed efficiency in poultry production. However, many countries include Indonesia now ban the use of AGP and attempts are made to replace the antibiotic to maintain good performances of broilers. Plant bioactives is one of the alternatives that could replace the AGP. An experiment was conducted in an attempt to replace the AGP in broiler feed with a mixture of some plant bioactives<strong> </strong>(liquid smoke of cashew nutsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Based on this knowledge, researchers now work towards the recognition of specific bacterial populations that definitively enhance animal growth and the identification of approaches and resources to achieve a desired microbiota. Following the widespread use of antimicrobial growth promoters in animal feed and the observation of their impact on poultry and swine production, several parameters such as weight gain, feed conversion rate, intestinal morphology, microbiota composition, production of digestive enzymes, immune response, and carcass quality have been established as growth-promoting indicators (summarized in Table S1 ) [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Modes Of Action Of Antibiotics To Promote Animal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this knowledge, researchers now work towards the recognition of specific bacterial populations that definitively enhance animal growth and the identification of approaches and resources to achieve a desired microbiota. Following the widespread use of antimicrobial growth promoters in animal feed and the observation of their impact on poultry and swine production, several parameters such as weight gain, feed conversion rate, intestinal morphology, microbiota composition, production of digestive enzymes, immune response, and carcass quality have been established as growth-promoting indicators (summarized in Table S1 ) [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Modes Of Action Of Antibiotics To Promote Animal Growthmentioning
confidence: 99%
“…Most studies on the use of probiotics in animal feed have reported a wide variety of beneficial effects on animal growth and health. Along with the beneficial impact on gut microbiota and inflammation, it was observed that probiotics can reduce diarrhea and improve feed digestion by producing enzymes or by promoting digestive enzyme secretion in the intestines [ 60 , 134 , 142 , 149 ]. However, several concerns with some probiotic-based products such as variations in the quality and dose of probiotics, poor survival rate in the stomach, inactivation during feed manufacturing, transport, or storage, allergenicity, potential crosstalk between probiotics, pathogens and epithelial cells, and transmission of antibiotic-resistance genes can limit their use [ 140 , 147 , 149 , 150 ].…”
Section: Alternatives To Antibiotics As Growth Promotersmentioning
confidence: 99%
“…mineral salts such as iron, phosphorus, and magnesium. Turmeric also contains 9.61% curcumin compounds (Sinurat et al, 2009). Curcumin functions in regulating fat metabolism.…”
Section: Feed Conversion Rate (Fcr) and Feed Efficiency (Fe)mentioning
confidence: 99%
“…Turmeric is a type of turmeric rhizome-producing plant that thrives in Indonesia (Arifin, Setiawati, Bambang, & Utomo, 2015). Turmeric also contains 9.61% curcumin compounds (Sinurat et al, 2009). Curcumin functions in regulating fat metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, plant extracts have been used as a substitute for AGP [5]. Indonesia, as a tropical country, has a variety of plants containing bioactive compounds which may potentially serve as antibacterial and antifungal agents, such as Psidium guajava roots and leaves [6], cashew shell extract [7], mangosteen extract [8], Plumeria rubra flower and leaf extract [9], Phyllanthus niruri L. extract [10], and clove (Syzygium aromaticum) leaf extract [11].…”
Section: Introductionmentioning
confidence: 99%